2021
DOI: 10.1038/s41598-021-81172-0
|View full text |Cite
|
Sign up to set email alerts
|

Metformin exerts anti-cancerogenic effects and reverses epithelial-to-mesenchymal transition trait in primary human intrahepatic cholangiocarcinoma cells

Abstract: Intrahepatic cholangiocarcinoma (iCCA) is a highly aggressive cancer with marked resistance to chemotherapeutics without therapies. The tumour microenvironment of iCCA is enriched of Cancer-Stem-Cells expressing Epithelial-to-Mesenchymal Transition (EMT) traits, being these features associated with aggressiveness and drug resistance. Treatment with the anti-diabetic drug Metformin, has been recently associated with reduced incidence of iCCA. We aimed to evaluate the anti-cancerogenic effects of Metformin in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 62 publications
(93 reference statements)
0
19
0
1
Order By: Relevance
“…The activation of AMPK reduces cell proliferation through negatively regulates mTOR signaling (43). Recent results showed that NT-1044 exhibited higher AMPK activation than metformin at the same dosage in differentiated human adipocytes (44).In its role as an AMPK activator, the anti-tumorigenic activity of NT-1044 appears similar to that of metformin, which has been shown to significantly decrease proliferation of several human cancer cell lines in vitro, including endometrial cancer (25,26,(45)(46)(47). Since AMPK negatively controls mTOR activation and mTOR is a downstream effector of AKT, Activation of AMPK is considered to be a possible therapeutic target for cancers that contain high AKT activity (48).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of AMPK reduces cell proliferation through negatively regulates mTOR signaling (43). Recent results showed that NT-1044 exhibited higher AMPK activation than metformin at the same dosage in differentiated human adipocytes (44).In its role as an AMPK activator, the anti-tumorigenic activity of NT-1044 appears similar to that of metformin, which has been shown to significantly decrease proliferation of several human cancer cell lines in vitro, including endometrial cancer (25,26,(45)(46)(47). Since AMPK negatively controls mTOR activation and mTOR is a downstream effector of AKT, Activation of AMPK is considered to be a possible therapeutic target for cancers that contain high AKT activity (48).…”
Section: Discussionmentioning
confidence: 99%
“…In cultures of human cholangiocarcinoma cells, and at concentrations corresponding to plasma levels of metformin in diabetic patients, metformin inhibited proliferation and cell migration and induced apoptosis. Expression of vimentin (mesenchymal marker) and EMT genes was downregulated and expression of cytokeratin-19 (epithelial marker) was upregulated ( 172 ). The findings from the multiple ongoing trials ( 173 ) may convey a deeper understanding of the anti-tumor function of metformin in the near future.…”
Section: Caf and Tam In Immunotherapy And Anti-angiogenesismentioning
confidence: 99%
“…Buhrmann and co-workers showed that RES inhibited the TNF-b-induced EMT as demonstrated by suppressing EMT factors (up-modulating vimentin and slug, down-modulating E-cadherin) in colorectal cancer cells through preventing the FAK/NF-kB activation as proved by downregulation of MMP-9 and C-X-C motif chemokine receptor 4 (CXCR4) which are the NF-kB-dependent of tumor-promoting factors (17,18). Moreover, it has been reported that cancer stem cells (CSCs) had stem cell characteristics like pluripotency, selfrenewal, invasion, motility (121)(122)(123)(124). CD133, CD44 and aldehyde dehydrogenase gene 1 (ALDH1), as molecules associate with CSCs, are widely used to mark CSCs (125,126).…”
Section: Colorectal Cancermentioning
confidence: 99%